Political Campaign Strategy for President Joko Widodo's Son During COVID-19 Pandemic - Dimas Subekti (Universitas Medan Area, 2022)
The issue of dynastic politics and the violation of health protocols aimed at Gibran Rakabuming Raka did not hinder his victory as mayor of Surakarta. Therefore, this study aims to explain the political campaign strategy of the mayor of Surakarta Gibran Rakabuming Raka in the 2020 simultaneous regional head elections during the COVID-19 pandemic. This type of research is qualitative, using a descriptive approach. This study uses library research data collection techniques. The findings of this study are Gibran Rakabuming Raka's political campaign as the son of President Joko Widodo in general succeeded in implementing the five stages of the political campaign. As a result, he won the 2020 Surakarta Mayor election. However, there are interesting notes found at the legitimacy stage. In the context of Gibran Rakabuming Raka's political campaign, legitimacy is obtained directly through political parties which is not appropriate in the theory of The Five Functional Stages of Development. Therefore, as a contribution to reform in the theory of political campaign strategy, the candidate's legitimacy stage must directly have support from the side of political power to clarify his position in the nomination.